BALANCE OF Thl/Th2/Th9/Thl7/Th22 CYTOKINES IN POST-OPERATION PERIOD IN PATIENTS WITH MALIGNANT TUMOR OF LIVER - G. B. Aleksanyan; E. A. Akhmatova; N. K. Akhamtova; E. A. Kurbatova; D. N. Panchenkov; V. V. Zverev (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. Evaluate cytokine status in patients with malignant liver cells after surgery. Materials and methods. 33 patients aged 35 to 76 years were included into the study. Blood was obtained before the operation and in the post-operation period: after 6 and 24 hours and at day 7. Cytokine profile (IL-lb, IL-2, TNF-a, IFN-y, IL-12p70, IL-4, IL-5, IL-6, IL-10, IL-13, IL-9, II- 17a, IL-22) was evaluated using Multiplex-13 system (Bender MedSystems, Austria). Results. Inpatients levels of all the studied cytokines (Thl/Th2/Th9/Th 17/Th22) were already increased before the operations, that gives evidence of the presence of an inflammatory process connected with activation ofimmune system effectors. Conclusion. Disbalance of cytokine system helper cells resulting in functional and organic alterations through induction of the “cytokine storm” may aggravate the state of these patients. Further studies on the correction of cytokine system in these patients are thus needed.